THEORETICAL STUDY OF HYDROMAGNETIC SQUEEZE FILM ROUGH TRUNCATED CONICAL PLATES WITH KOZENY-CARMAN MODEL BASED POROUS STRUCTURE - Adeshara Jatinlumar Vasantlal; Patel Hardik P; G M Deheri; R M Patel (Proceedings on Engineering Sciences, 2020)
Assuming that the surfaces of the truncated conical plates are transversely rough and considering the porous structure based on the Kozeny-Carman model, in the transverse magnetic field, the issue of the squeeze film between electrically conductive rough porous surfaces with electrically conductive lubricant is analyzed. The roughness of the surface of the bearing is dependent on a stochastic random variable with non-zero mean, variance and skewedness. After stochastically averaging the equation of Reynolds with regard to the parameter of random roughness, the pressure distribution, which in turn leads to the load carrying capacity, is solved with suitable boundary conditions. The analyses are displayed in both graphic and tabular form. It is known that the bearing roughness is transversely rough in general. Nonetheless, in the case of negative skewed roughness, the condition can be restored to some level by choosing the conductivities of the plate, if there is a negative variance. It is also found that even when there is no flow the magnetic field bearing can sustain a load.